Seroprevalence of Anti - Toxoplasma Antibodies Among Women of Child Bearing Age in Duhok Province - MOSTAFAAL-ATROSHI, AWAT ABDULL AZIZ; MERO, WIJDAN M. S. (Science Journal of University of Zakho, 2013)
A total number of 1146 blood samples taken randomly from single and married women at child bearing age of different ages, different socioeconomic and educational classes in Duhok city. They were examined to detect anti-toxoplasma IgG and IgM Abs by using LAT and ELISA tests. The rate of seroprevalence was 38.7 % by using LAT, while it was 27.7 % by using ELISA IgG. On the other hand, the rate of anti-toxoplasma IgM Abs was only 0.4 % by using ELISA. Significant differences were observed in rate of seropositivity between single and married women, and also between various age groups, the highest rate (45.3%) was observed among the age group 31-35 years. Also significant seropositive rates were observed between all educational levels with the highest rates (36.4% and 34.2%) being among illiterate and house wives, respectively. Contact with cats or eating undercooked meat has no effect on seropositivity rate. Regarding married status, pregnant women showed highest seropositivity (49.7%) especially at first trimester of gestation.